2014
DOI: 10.1248/cpb.c13-00524
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Physicochemical Properties of Fine Globular Granules Prepared by a Multi-functional Rotor Processor

Abstract: Multiple regression analysis (MRA) and principal component analysis (PCA) have been used in the present study to examine the relationships between the operational conditions of a unique multi-functional rotor processor, material attributes such as water content during granulation, and a series of associated micromeritics, including the flowability, granule mean size and granule density values. A variety of different operational conditions were tested, including the binder flow rate, atomization pressure, slit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
4
1
Order By: Relevance
“…Although the rotating speed (X 3 ) had been found to have no effect on the granular roundness during our previous study involving a drug-free formulation, 7) the results of the current study were inconsistent with this finding because the rotating speed was found to have a negative effect on the granule roundness. Furthermore, previous results from the literature revealed similar contradictorily results.…”
Section: )contrasting
confidence: 99%
See 2 more Smart Citations
“…Although the rotating speed (X 3 ) had been found to have no effect on the granular roundness during our previous study involving a drug-free formulation, 7) the results of the current study were inconsistent with this finding because the rotating speed was found to have a negative effect on the granule roundness. Furthermore, previous results from the literature revealed similar contradictorily results.…”
Section: )contrasting
confidence: 99%
“…7) Taken together, these results suggest that the GX system could be used to develop a manufacturing process for the preparation of highly drug-loaded fine globular granules with a particle size of less than 200 µm.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Before scale-up study on a complex fluidized-bed granulator, the critical process parameter for determining particle size must be known to obtain the desired particle size. Kimura et al reported that the spraying air pressure was identified as one of critical process parameters in granulation process, using a multi-functional rotor processor, Granulex ® [5,6]. We focused on the spraying air pressure as well as the case of using Granulex ® .…”
Section: Critical Process Parameter For Particle Sizementioning
confidence: 99%
“…3. One of the problems during preparation of fine particles is the production of largely agglomerated particles [5,6,9] or imperfectly coated particles [9]. It should be noted, however, that in all cases treated FAM had homogenous distributions without largely agglomerated particles or imperfectly uncoated particles.…”
Section: Fig 2: Relationships Between Spraying Air Pressure and Partmentioning
confidence: 99%